Morphometric characteristics of organs of female chickens (Pazo de Vilane) supplemented with Curcuma longa - D. F. Maldonado Arias; J. M. Mira-Naranjo; D. I. Cajamarca Carrazco; J. I. García-Guerra; M. F. Baquero-Tapia; M. E. Sánchez-Salazar; E. M. Melendres-Medina; A. N. Montalvan-Cobo; S. A. Guamán-Rivera (Brazilian Journal of Biology)
Abstract The breeding and exploitation of chickens at the backyard or commercial family level is an activity of great economic relevance for families in Ecuador. In addition to providing protein of high biological value for food security, it revalues local food resources that could provide productive benefits. With this objective, a study has been conducted in order to explore the effect of C. longa flour on the final weight as well as morphometric characteristics of the organs of female chickens. Therefore, a total of 200 birds were randomly distributed into four homogeneous groups, being Control, basal diet only, followed by T1, basal diet + 1 g/d, T2, basal diet + 2 g/d and T3, basal diet + 3 g/d of C. longa. The data analyzed under a general linear model yielded that including C. longa between 1 or 2 g/d did not differ in the final weight compared to the control (2763 ± 28 g, on average; P < 0.32). In the morphometry of the upper organs, T1 indicated a shorter length of the esophagus (3.7 ± 0.5 mm; P < 0.002) and gizzard (4.9 ± 0.3 mm), but with a larger heart than the other treatments (P < 0.02). In addition, differences were evident in the liver, gallbladder and cecum (P = 0.01 to 0.001) that were more marked when C. longa was administered between 1 or 2 g/d. In conclusion, supplementation of female chickens with C. longa proved to be a potential option to have greater final weights with important findings in the morphometric characteristics that could improve different aspects of their development, productivity and well-being. Therefore, more studies at the level of immunology and histology are recommended to support the benefits of C. longa.